Confronting Climate Uncertainty in Water Resources Planning and Project Design : The Decision Tree Framework - Ray, Patrick A.; Brown, Casey M. (Washington, DC: World Bank, 2015)
The Decision Tree Framework described in this book provides resource-limited project planners and program managers with a cost-effective and effort-efficient, scientifically defensible, repeatable, and clear method for demonstrating the robustness of a project to climate change. At the conclusion of this process, the project planner will be empowered to confidently communicate the method by which the vulnerabilities of the project have been assessed, and how the adjustments that were made (if any were necessary) improved the project’s feasibility and profitability.